2019
DOI: 10.11604/pamj.2019.34.15.17803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alvarado score in diagnosing acute appendicitis

Abstract: Using a practical scoring system for diagnosing acute appendicitis can help reduce the rate of unnecessary surgery. This prospective study was carried out to evaluate Alvarado scoring system for diagnosing of acute appendicitis in our set up. Out of total 100 patients, appendicitis was confirmed in 80 patients, thus giving negative appendectomy rate of 20% (male 6%, female 14%). Perforation rate was 4%. Positive predictive value was 89%. The sensitivity was 54% and specificity 75%. Alvarado score is not a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
7
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 5 publications
4
23
7
9
Order By: Relevance
“…The predictive values of Alvarado score in the current study are consistent with the results obtained by Pogorelic et al's sensitivity, specificity, PPV of 89%, 59%, 93.1%, and 46%, respectively [5]. Dey et al, as well as Nanjundaiah et al, Al Awayshih and associates in mixed population studies also observed comparable findings [4,11,18]. In this study, the decision to operate was based on the clinical judgement of the surgeon with a negative appendicectomy rate of 19% which was comparable to rates obtained in settings where CT scan is not routinely deployed in the diagnosis of acute appendicitis [11,13,14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The predictive values of Alvarado score in the current study are consistent with the results obtained by Pogorelic et al's sensitivity, specificity, PPV of 89%, 59%, 93.1%, and 46%, respectively [5]. Dey et al, as well as Nanjundaiah et al, Al Awayshih and associates in mixed population studies also observed comparable findings [4,11,18]. In this study, the decision to operate was based on the clinical judgement of the surgeon with a negative appendicectomy rate of 19% which was comparable to rates obtained in settings where CT scan is not routinely deployed in the diagnosis of acute appendicitis [11,13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Dey et al, as well as Nanjundaiah et al, Al Awayshih and associates in mixed population studies also observed comparable findings [4,11,18]. In this study, the decision to operate was based on the clinical judgement of the surgeon with a negative appendicectomy rate of 19% which was comparable to rates obtained in settings where CT scan is not routinely deployed in the diagnosis of acute appendicitis [11,13,14]. The rate however drops to as low as 2.5-7.5% in settings where CT scan is routinely deployed [19,20].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, given the low specificity of this parameter, normal range CRP cannot exclude acute appendicitis [ 19 ]. Considering these contradictory results and questioned diagnostic value of Alvarado system [ 20 , 21 ], the combination of Alvarado system and CRP (Alvarado + CRP) was assessed in our study. The sensitivity, specificity, PPV and NPV of the Alvarado + CRP system were 79%, 7%, 92%, and 20%, respectively.…”
Section: Discussionmentioning
confidence: 99%